SPP: portable power technologies for the dismounted soldier - Sousa, Carlos (2011)
The project aims at the development of a portable power system as standard equipment for defence use, and is being developed by a Portuguese consortium leaded by SRE, a fuel cell developer, LNEG (Portuguese National Laboratory for Energy and Geology) and EID (Electronics and Telecommunications for Army) through a SRE/ Ministry of Defence contract. The system uses a SRE H2 PEM Fuel Cell and a Li battery buffer (30Wh). The fuel is provided by an on board H2 generator based on chemical hydrides, aiming to provide 72h autonomy to the dismounted soldier. Main project constraints and challenges are the power density (both gravimetric and volumetric) and the operation under severe atmospheric conditions. A field test pre-series shall take place by the end of 2010 with probable commercialization foreseen by early 2012.